Authentic leadership and employee engagement: The role of employee well-being - Koon, Vui Yee*; Ho, Tsu Sin (IOS Press, 2021)
BACKGROUND/OBJECTIVE:To understand how perceived authentic leadership translates into work engagement, this study hypothesize that perceived authentic leadership facilitates positive conditions of well-being, which in turn predict employee work engagement. This study asserts that each of the three mediating paths comprising life, workplace, and psychological well-being, is expected to mediate the relationship based on the conservation of resources (COR) theory and relational perspective. METHODOLOGY:Data were collected from the two-wave survey of 150 full-time employees and analyzed using the PROCESS macro in SPSS. An additional analysis to identify well-being sentiment was conducted using NodeXL with Twitter data. RESULTS:The results indicated only workplace well-being has a mediational effect between perceived authentic leadership and work engagement. The additional analysis found that workplace well-being is the central tenet of interaction between people in social media. CONCLUSIONS:These findings demonstrate the importance of workplace well-being in promoting work engagement.